PERAN CORPORATE GOVERNANCE TERHADAP KUALITAS PELAPORAN KEUANGAN – A SYSTEMATIC LITERATURE REVIEW - Raharjo, Hana Jovita; Dewayanto, Totok (Diponegoro Journal of Accounting, 2024)
Corporate governance has a role in the quality of financial reporting therefore companies need to use corporate governance to enhance managerial oversight and stop opportunistic conduct. This study aims to determine the role of internal audit, CEO, board of directors, supervisory board, share ownership, audit committee, and public accounting firm on financial reporting quality and research directions that can be explored in the future. The systematic review methodology used in this study is a qualitative method. This research used secondary data derived from the results of research published in journals in the form of online articles. This systematic literature review covers twenty English- language articles published in 2019-2023 and included in Scopus indexed journals. The results showed that some corporate governance mechanisms consistently show that their characteristics play an important role in the quality of financial reporting, the impact of various characteristics of various other corporate governance mechanisms is different.